Restraining fluoride loss from NaYF4:Yb3+,Er3+ upconverting nanoparticles in aqueous environments using crosslinked poly(acrylic acid)/poly(allylamine hydrochloride) multilayers - Palo Emilia; Salomäki Mikko; Lastusaari Mika (Academic Press Inc., 2022)
The use of upconverting nanoparticles in various applications in aqueous media relies on their surface modifications as most synthesis routes yield hydrophobic particles. However, introducing upconverting nanoparticles in aqueous solutions commonly results in the quenching of their luminescence intensity and in the worst case, disintegration of the nanoparticles. We demonstrate the use of poly(acrylic acid) and poly(allylamine hydrochloride) as a protecting layer-by-layer coating for the upconverting NaYF4:Yb3+,Er3+ nanoparticles. The formation and crosslinking of the bilayer coating was confirmed with Fourier transform infrared spectroscopy, thermal analysis and zeta potential. The release of internal fluoride ions from the nanoparticle structure and subsequent particle disintegration was decelerated especially by crosslinking the bilayer coating on the surface. In addition, we studied the effect of the coating on the upconversion luminescence properties and learned that with additional fluoride ions present during the layer-by-layer assembly the most intense enhancement in the luminescent intensity is obtained. This is due both to not allowing the disintegration of the particles during the surface modification process as well as preventing the water molecules accessing the surface by crosslinking the bilayer coating.